"Acting Ethnic"—Performance of ethnicity and the process of ethnicization. (October 2017) - Grosswirth Kachtan, Dana
This paper examines the process of "acting ethnic", and demonstrates that, in certain circumstances, people act in keeping with an ethnic identity. Based on a study of two infantry brigades in the Israeli army (the IDF), the paper shows how organizational ethnic culture forms the basis of the process of "acting ethnic". This paper highlights the tendency in certain situations to suspend nonethnic privileges by adopting an ethnic identity and in addition, to exaggerate ethnic performance. Moreover, it is argued that "acting ethnic" is a collective performance, aimed not only at belonging to the group, but also as a means of maintaining and reproducing ethnic identity and asserting a legitimate alternative to the hegemonic identity.